A Cocatalyst Strategy to Enhance Ruthenium‐Mediated Metathesis Reactivity towards Electron‐Deficient Substrates. Issue 29 (16th May 2022) - Si, Guifu; Tan, Chen; Chen, Min; Chen, Changle
Abstract: Ruthenium‐mediated olefin metathesis has been widely applied for the synthesis of various organic molecules and polymers. Inspired by the cocatalyst strategy for olefin polymerization, here we demonstrate that the abstraction of a chloride ion from various commercially available ruthenium catalysts significantly enhances their reactivity towards electron‐deficient internal olefins. This cocatalyst strategy can be implemented in ethenolysis and cross‐metathesis reactions of FG‐CH=CH‐FG type substrates bearing electron‐withdrawing groups and the synthesis of telechelic polymers that can be converted to polyethylene‐like materials with closed‐loop recycling properties. The copolymerization of cyclic substrate with cycloolefins followed by hydrogenation afforded polyolefin materials with in‐chain break points. Interestingly, switchable catalysis was achieved in the absence and presence of a cocatalyst, which allowed the polymer microstructure and material properties to be fine‐tuned. Abstract : The abstraction of a chloride ion from various commercially available ruthenium catalysts significantly enhances their reactivity towards electron‐deficient internal olefins. This cocatalyst strategy can be implemented in ethenolysis and cross‐metathesis reactions, as well as the synthesis of polyethylene‐like materials with closed‐loop recycling properties.